Inactivation of photosynthetic cyclic electron transports upregulates photorespiration for compensation of efficient photosynthesis in Arabidopsis - Chen, Qi; Lan, Yixin; Li, Qinghua; Kong, Mengmeng; Mi, Hualing (Frontiers in Plant Science, 2023)
Plants have multiple mechanisms to maintain efficient photosynthesis. Photosynthetic cyclic electron transports around photosystem I (CET), which includes the PGR5/PGRL1 and NDH pathways, and photorespiration play a crucial role in photosynthetic efficiency. However, how these two mechanisms are functionally linked is not clear. In this study, we revealed that photorespiration could compensate for the function of CET in efficient photosynthesis by comparison of the growth phenotypes, photosynthetic properties monitored with chlorophyll fluorescence parameters and photosynthetic oxygen evolution in leaves and photorespiratory activity monitored with the difference of photosynthetic oxygen evolution rate under high and low concentration of oxygen conditions between the deleted mutant PGR5 or PGRL1 under NDH defective background (pgr5 crr2 or pgrl1a1b crr2). Both CET mutants pgr5 crr2 and pgrl1a1b crr2 displayed similar suppression effects on photosynthetic capacities of light reaction and growth phenotypes under low light conditions. However, the total CET activity and photosynthetic oxygen evolution of pgr5 crr2 were evidently lower than those of pgrl1a1b crr2, accompanied by the upregulation of photorespiratory activity under low light conditions, resulting in severe suppression of photosynthetic capacities of light reaction and finally photodamaged phenotype under high light or fluctuating light conditions. Based on these findings, we suggest that photorespiration compensates for the loss of CET functions in the regulation of photosynthesis and that coordination of both mechanisms is essential for maintaining the efficient operation of photosynthesis, especially under stressed conditions.